Effects of planting density and nitrogen application on the growth of Xanthium strumarium subsp. sibiricum under manganese stress - Pan, Gao; He, Ling; Yu, Zixin; Chen, Meng; Gao, Yidan; Li, Zhiliang; Liu, Wensheng (Frontiers in Plant Science, 2026)
IntroductionPlanting density and nitrogen (N) application play important roles in plant growth and heavy metal uptake under stress conditions. However, their mechanisms of interaction remain unclear.MethodsTo investigate the effects of planting density and N application on plant growth and manganese (Mn) toxicity alleviation, a pot experiment was conducted to study the variations in growth, physiological and biochemical characteristics, and Mn uptake of Xanthium strumarium subsp. sibiricum under different Mn concentrations (0.05 and 10 mmol L-1), planting densities (3, 42, and 84 individuals m⁻²), and N application rates (0, 5, and 30 mmol L-1).ResultsThe results showed that with increasing planting density and N application under Mn stress, individual plant biomass first increased and then decreased, while biomass per m2 increased. The contents of photosynthetic pigments (chlorophyll a, chlorophyll b, and carotenoids), osmotic adjustment substances (soluble sugars, soluble proteins, and free proline), and antioxidant enzyme activities (SOD, POD, and CAT) also increased initially and then declined. Conversely, the contents of malondialdehyde and relative electrical conductivity decreased. Mn concentrations in the roots, stems, leaves, fruits, and individual plants decreased, whereas total Mn uptake increased with higher planting density and exhibited an initial rise followed by a decline with increasing N application.DiscussionThis study demonstrates that planting density and N applications significantly affect Mn accumulation and the tolerance of Xanthium strumarium subsp. sibiricum to Mn stress, primarily by promoting the accumulation of osmotic adjustment substances, enhancing antioxidant enzyme activities, and reducing Mn concentration in plant tissues. These findings highlight that appropriate N management and planting density can mitigate Mn toxicity and improve plant resilience under Mn stress.